Diagnostic yield of post-bronchoscopy sputum for diagnosing pauci-bacillary pulmonary tuberculosis - Joung Ha Park; Kyung-Wook Jo; Tae Sun Shim; Sung-Han Kim (Annals of Medicine, 2021)
AbstractBackground A few studies have mentioned that post-bronchoscopy sputum (PBS) could improve the diagnostic yield in pauci-bacillary pulmonary tuberculosis (PTB). Therefore, we evaluated the diagnostic yield of PBS for diagnosing pauci-bacillaryPTB.Methods Clinical data of immunocompromised adult patients with pauci-bacillary PTB were retrospectively retrieved at a tertiary hospital in Seoul, South Korea over a 5-year period. We analyzed patients who underwent bronchoscopy examinations for diagnosing pauci-bacillary PTB.Results Ninety patients were finally analyzed. Of these patients, 76 patients were tested with PBS. Six (8%) of these patients had positive results on AFB smear of PBS alone. Additionally, 52 patients (68%) had positive results on mycobacterial culture and 12 (16%) had positive results on mycobacterial culture of PBS exclusively. Therefore, in this study population, a total of 18 patients (20%) were finally diagnosed as having PTB with PBS results only, even though AFB smear microscopy and culture of other specimens had negative results.Conclusions PBS could improve the diagnostic yield by 20% when diagnosing pauci-bacillary PTB. In addition, about 8% of the patients could be diagnosed rapidly because of AFB smear microscopy positivity for PBS. Therefore, PBS use should be considered as a complementary diagnostic approach in patients with suspected pauci-bacillary PTB.